Sustainable Human Development at the Municipal Level: A Data Envelopment Analysis Index - Lima, Pedro A. B. [UNESP]; Paião Júnior, Gilberto D. [UNESP]; Santos, Thalita L. [UNESP]; Furlan, Marcelo; Battistelle, Rosane A. G. [UNESP]; Silva, Gustavo H. R. [UNESP]; Ferraz, Diogo [UNESP]; Mariano, Enzo B. [UNESP] (MDPI, 2022)
The development of indexes for human development and environmental sustainability issues are an emerging topic in the current literature. However, the literature has put less emphasis on municipal indexes, which is the focus of this research. In this paper, we considered municipal environmental management as the adoption of environmental activities and the development of infrastructural and technical capacities in municipalities. This article aims to create a sustainable human development index with municipal data from the state of São Paulo in Brazil. Using information from the Municipal Human Development Index (IDHm) and the GreenBlue Municipal Program (PMVA), we applied the data envelopment analysis (DEA) technique to connect human development and environmental sustainability in 645 Brazilian municipalities. Our findings show that regions with higher human development present better DEA scores on the Sustainable Human Development Index. In contrast, regions with a low or a middle level of human development do not present significant change considering both dimensions. Moreover, our findings reveal that PMVA certification has a different and statistically significant impact on the DEA score considering certified, qualified, or not qualified regions. We found similar results for urbanized and service-oriented municipalities. Our indicator is an essential and straightforward tool for regional policymakers, helping to allocate resources and to find human development and environmental sustainability benchmarks among developing regions.
Keywords: Data envelopment analysis (DEA); Environmental manage-ment; Environmental program; Human development; Index; Infrastructure; Sustainability; Urban management